Proposal for a System to Accredit Small and Medium-Sized Enterprises - Jiménez-Montero, Daniel (2009)
One of the main characteristics of small and medium-sized enterprises in Costa Rica is the lack of documentation regarding their day-to-day operations. This represents a weakness for these types of businesses, as their survival depends on the individuals who hold the company’s information in their minds. Given this situation, there is a need to create an accreditation system that empowers companies to document their respective operations and that also certifies the company’s level of documentation. In this way, those interested in learning about a certified company can do so thanks to the information provided by this accreditation system. The content of this document revolves around a proposal for an accreditation system that meets the need described in the previous paragraph.